PANCASILA DALAM KEHIDUPAN EKONOMI - Istiyanti, Istiyanti (Universitas Muhammadiyah Magelang, 2010)
Since Pancasila accepted as a principle of living in a society, nation and state, then the Ideological life of the nation has been steady and serene, an atmosphere of life that is very helpful to create excitement to the life of the nation in its various aspects. In the meantime conceptual thoughts about Pancasila economy began to grow in the New Order era to the present discussion Reform Order Pancasila economy more widely discussed by experts and practitioners. Even the recent House of Representatives discusses more intense, particularly in relation to the elaboration of the understanding of economic democracy. Through this paper, the authors will discuss the extent to which the ideology of Pancasila has actually penetrated into the heart of economic beings citizen of Indonesia. In other words, we want to see how far the concept of Pancasila economyincreasingly accepted and implemented them in real economic life of everyday society, both economic actors directly and government and all members of society.